PENGARUH BUDAYA ORGANISASI, SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DAN SISTEM MANAJEMEN MUTU ISO 9001 TERHADAP KINERJA KARYAWAN PADA PT. PACIFIC MEDAN INDUSTRI - Eviyanti Tarigan (Universitas Islam Islam Sumatera Utara, 2020)
The core of this study is how the effect of organizational culture, SMK3 and ISO 9001 to the employee's performance in Pacific Medan Industry Company. Purpose of the study is to know and analyse the effect of organizational culture SMK3, quality management system ISO 9001 to the employee's performance in Pacific Medan Industry Company. This research using quantitative approach is done by collecting numeral data. That numeral data is then processed and analysed to get scientific information behind those numbers. Data that used in this research were gotten from the questionnaire results to 90 respondents as the tool to collect data. This research data use survey methods with data analysis techniques using simple linear regression and correlation people to know correlation between variable x to variable y and also doing hypothesis test to know the effect of each variable. Result of the research show that organizational culture as variable X1 gives positive and significant effect to employee's performance in Pacific Medan Industry Company with regression coefficient value 0,315 or 31,5%. SMK3 as variable X2 gives positive and significant effect to employee's performance in Pacific Medan Industry Company with regression coefficient value 0,238 or 23,8%. Variable X3 ISO 9001 gives positive and significant effect to employee's performance in Pacific Medan Industry Company with regression coefficient value 0,601 or 60,1%. Organizational culture X1, SMK3 X2 and ISO 9001 X3 give significant effect to employee's performance variable y in Pacific Medan Industry Company. Determination coefficient value 0,421 which means that employee's performance changing able to be explained by change in organizational culture variable X1, SMK3 X2 and ISO 9001 X3 are 42,1%.